Sistem Peminjaman Barang Menggunakan QR Code Berbasis Aplikasi Android - Purnomo, Sidiq; Alijoyo, Franciskus Antonius (Prodi Sistem Informasi Universitas Dharma Andalas, 2024)
The mechanism of borrowing items in an institution or company is an important task to be carried out because with the right and organized system, the availability of items, which are assets of the institution and/or company, can be maximized. Information regarding the availability and completeness of items can be obtained from the item borrowing data. A poorly implemented borrowing mechanism can result in unrecorded borrowed assets, leading to loss and ineffective use of items. Several studies have been conducted on item borrowing systems that utilize information technology, including web-based and Android-based systems. Therefore, this study aims to enhance the existing item borrowing system, where the system will utilize qr codes and a real-time firebase database, and will be based on the Android platform. The method used in designing this system is the waterfall method, which follows a sequential software development life cycle approach starting from the stages of analysis, design, implementation, testing, and maintenance. With this system, it is expected that item borrowing in institutions and/or companies will become more efficient and organized, allowing all employees to maximize the use of items, and enabling them to be aware of the status of items that are being borrowed or are scheduled to be borrowed